2006
DOI: 10.2460/ajvr.67.4.723
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the urodynamic and hemodynamic effects of orally administered phenylpropanolamine and ephedrine in female dogs

Abstract: Oral administration of phenylpropanolamine once daily or ephedrine twice daily increased urethral resistance in clinically normal dogs and may be recommended for management of urethral sphincter mechanism incompetence. Treatment efficacy may be assessed after 1 week. Dogs with concurrent cardiovascular disease should be monitored for blood pressure while receiving alpha-adrenergic agents because of the effects on diastolic and mean arterial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
0
11
2
Order By: Relevance
“…In contrast, a decrease in heart rate associated with an increased arterial pressure consecutive to PPA administrations was reported in some studies (8,19,20). Although arterial pressure was not measured in this study and arterial hypertension has not been reported clinically at recommended dosage in bitches, authors of this study share the previously reported concerns about cautious use of drugs that are capable of inducing tachycardia in animals receiving α-adrenergic agents (8,9). In addition, serial blood pressure monitoring in dogs that are receiving α-adrenergic agents is recommended.…”
Section: Discussioncontrasting
confidence: 32%
See 2 more Smart Citations
“…In contrast, a decrease in heart rate associated with an increased arterial pressure consecutive to PPA administrations was reported in some studies (8,19,20). Although arterial pressure was not measured in this study and arterial hypertension has not been reported clinically at recommended dosage in bitches, authors of this study share the previously reported concerns about cautious use of drugs that are capable of inducing tachycardia in animals receiving α-adrenergic agents (8,9). In addition, serial blood pressure monitoring in dogs that are receiving α-adrenergic agents is recommended.…”
Section: Discussioncontrasting
confidence: 32%
“…Recurrence of incontinence associated with a decrease in urethral response is observed after a prolonged administration of multiple doses PPA (23) and it has been proposed that desensitization of urethral α-adrenergic receptors may occur in dogs treated multiple times daily with PPA or in dogs receiving prolonged treatment (8). In accordance with the results of the current study, Claeys et al (9) followed up 5 bitches on single daily PPA treatment for a mean of 20.8 mo and observed no recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of pseudoephedrine, a stereoisomer of ephedrine that is a non-cathecholamine sympathomimetic agent, enhances release of norepinephrine from sympathetic neurons and directly stimulates both alpha and beta adrenoceptors [6]. This agent has been shown to increase urethral resistance and the urethral pressure profile in animal and human studies [5,6]. Through its effect on alpha receptors of the bladder neck and internal sphincter, pseudoephedrine prevents the relaxation of the bladder neck and thus improves continence in children.…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine ephedrine may be used to help control urinary incontinence in dogs and cats (Carofiglio et al, 2006). It may also be used to open up the air passages of the lungs and to relieve nasal congestion (Koss et al, 2002).…”
Section: Introductionmentioning
confidence: 99%